Routledge handbook of terrorism and counterterrorism - Silke, Andrew (Routledge, Taylor & Francis Group, 2019)
This book provides an overview of current knowledge and debates on terrorism and counterterrorism, as well as providing a benchmark for future research. The attacks of 9/11 and the 'global war on terror' and its various legacies have dominated international politics in the opening decades of the 21st century.